Entropy generation and characteristics of mixed convection in lid-driven trapezoidal tilted enclosure filled with nanofluid - Md. Shahneoug Shuvo; Mahmudul Hasan Hasib; Sumon Saha (Heliyon, 2022)
The investigation of steady, incompressible, laminar mixed convective fluid flow within two different types of tilted lid-driven trapezoidal enclosures filled with nanofluid composed of water and Al2O3 nanoparticles has been carried out in this paper. The upper wall of the enclosure is an isothermal cold surface that travels at a constant speed, while the bottom surface of the cavity maintains a constant high temperature. Non-dimensional governing equations along with the appropriate boundary conditions are solved using Galerkin finite element technique. Parametric simulation has been conducted by varying tilt angle of the base wall from 0° to 45°, Reynolds number from 0.1 to 103, Grashof number from 10−2 to 106, and Richardson number between 0.1 and 10 for three different cases. The streamlines and the isotherms are used to describe the fluid flow and heat transfer characteristics within the enclosure. Besides, the quantitative evaluations of thermal enhancement in terms of the average Nusselt number, average fluid temperature, and Bejan number of the enclosure are presented. Effects of base wall tilt angle and the presence of nanofluid on convection heat transmission characteristics as well as Bejan number are also explored.